Short Take: Lowering the Access Barriers to Ethnographic Methodology. Issue 2 (May 2021) - Pham, Tony V
Researchers based in low- and middle-income countries (LMIC) often cannot access conventional but high-priced ethnographic tools. I developed a low-cost methodology as an exercise in meeting the needs of both LMIC-based researchers and the broader qualitative community. As demonstrated in this proof of concept, ethnographic researchers should strive for a suite of open access software tools and common and affordable hardware to reduce inequities in knowledge generation and dissemination.